Acoustic methods for biofouling control: A review. (15th July 2015) - Legg, M.; Yücel, M.K.; Garcia de Carellan, I.; Kappatos, V.; Selcuk, C.; Gan, T.H.
Abstract: Biological fouling is a significant problem to the shipping industry causing significant increases in fuel, maintenance, and downtime costs. Environmental concerns associated with toxic antifouling coatings have led to studies on alternative methods of biofouling control. This paper provides a literature review on laboratory and sea trial studies, which have used acoustic techniques for biofouling control. To the best of the authors׳ knowledge, this is the first in depth literature review on this topic. Applications of the reviewed studies have included the inhibition of biofouling on vessel hulls and pipes and also treatment of ballast water. The studies have used transducers operating in the audio and ultrasonic frequency range and sparkers. Variations were found in these acoustic parameters, which were reported to provide inhibition. Some have reported that low ultrasonic frequencies (about 20 kHz) may be optimal. The potential effect of marine life is considered. The use of ultrasonic frequencies for biofouling control appear to be more desirable than audio frequencies since they are outside the hearing range of most marine life. More studies are needed on this topic, which are well documented in terms of the parameters used and efficiency of the trials. Abstract : Highlights: Review paper on biofouling control of marine structures using acoustic techniques. To the best of the authors knowledge, first in depth review paper on this topic. Acoustic methods reported to provide biofouling inhibition for marine structures. Acoustic devices operating at audio/ultrasonic frequencies and acoustic sparkers. Lower ultrasonic frequencies reported to provide better control of macrofouling.